Plethysmograph and interrupter resistance measurements in prematurely born young children. Issue 3 (20th October 2005) - Thomas, M R; Rafferty, G F; Blowes, R; Peacock, J L; Marlow, N; Calvert, S; Milner, A; Greenough, A
Abstract : Background: Airways obstruction in premature infants is often assessed by plethysmography, which requires sedation. The interrupter (Rint) technique does not require sedation, but has rarely been examined in children under 2 years of age. Objective: To compare Rint results with plethysmographic measurements of airway resistance (Raw) in prematurely born, young children. Design: Prospective study. Setting: Infant and Paediatric Lung Function Laboratories. Patients: Thirty children with a median gestational age of 25–29 weeks and median postnatal age of 13 months. Interventions and main outcome measures: The infants were sedated, airway resistance was measured by total body plethysmography (Raw), and Rint measurements were made using a MicroRint device. Further Raw and Rint measurements were made after salbutamol administration if the children remained asleep. Results: Baseline measurements of Raw and Rint were obtained from 30 and 26 respectively of the children. Mean baseline Rint values were higher than mean baseline Raw results (3.45 v 2.84 kPa/l/s, p  =  0.006). Limits of agreement for the mean difference between Rint and Raw were −1.52 to 2.74 kPa/l/s. Ten infants received salbutamol, after which the mean Rint result was 3.6 kPa/l/s and mean Raw was 3.1 kPa/l/s (limits of agreement −0.28 to 1.44 kPa/l/s). Conclusion: The poor agreement between Rint and Raw results suggests that Rint measurements cannot substitute for plethysmographic measurements in sedated prematurely born infants.